1999
DOI: 10.1002/(sici)1097-0169(1999)42:2<114::aid-cm3>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules, but not actin microfilaments, regulate vacuole motility and morphology in hyphae of Pisolithus tinctorius

Abstract: While it is now recognised that transport within the endomembrane system may occur via membranous tubules, spatial regulation of this process is poorly understood. We have investigated the role of the cytoskeleton in regulating the motility and morphology of the motile vacuole system in hyphae of the fungus Pisolithus tinctorius by studying (1) the effects of anti-microtubule (oryzalin, nocodazole) and anti-actin drugs (cytochalasins, latrunculin) on vacuolar activity, monitored by fluorescence microscopy of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…Morton et al (24) reported that latB affects the kinetics of actin polymerization by specifically binding to actin monomers and shifting the equilibrium to the disassembled state. In the filamentous fungus Pisolithus tinctorius, a perturbation of microfilament organization by latrunculin was shown (15), and in yeast and mammalian cells, receptor-mediated endocytosis was inhibited (3,19). We found that PAF transport into hyphal cells decreased with increasing concentrations of latB, and 50 g of latB/ml abolished internalization (Fig.…”
mentioning
confidence: 57%
“…Morton et al (24) reported that latB affects the kinetics of actin polymerization by specifically binding to actin monomers and shifting the equilibrium to the disassembled state. In the filamentous fungus Pisolithus tinctorius, a perturbation of microfilament organization by latrunculin was shown (15), and in yeast and mammalian cells, receptor-mediated endocytosis was inhibited (3,19). We found that PAF transport into hyphal cells decreased with increasing concentrations of latB, and 50 g of latB/ml abolished internalization (Fig.…”
mentioning
confidence: 57%
“…Nickel uptake is thoroughly documented in other fungal cells (Mohan et al, 1984;Joho et al, 1995;Nishimura et al, 1998;Dönmez & Aksu, 2001) and it has been localized within Hebeloma crustuliniforme ectomycorrhizas (Brunner & Frey, 2000). Vacuole vesiculation observed during Ni 2+ exposure also occurs by exposure to acids, cytoskeletal drugs, fixatives and fluorescent probes (Wilson et al, 1990;Cole et al, 1997Cole et al, , 2000Bachewich & Heath, 1999;Hyde et al, 1999), suggesting that this is a general response to toxins.…”
Section: +mentioning
confidence: 99%
“…These results suggest that Ni 2+ effects on MTs are related to the disruption of organelle tubularity and motility in P. involutus. Microtubule disruption causes vacuole vesiculation and mitochondrial fragmentation in other fungal cells (Steinberg et al, 1998;Bachewich & Heath, 1999;Hyde et al, 1999;McDaniel & Roberson, 2000;Khalaj et al, 2001;Fuchs et al, 2002). Interestingly MT disruption also triggers apoptosis through the mitochondrial pathway (Chen et al, 2002;Giacca, 2005. Instead of MTs, various fungal cells rely on the actin cytoskeleton for organelle motility and morphology (Morris & Hollenbeck, 1995; Simon et al, 1995;Gupta & Heath, 1997;Bachewich & Heath, 1998Suelmann & Fischer, 2000).…”
Section: +mentioning
confidence: 99%
“…MT-dependent processes that, if disrupted, are likely to affect the multicomponent tip growth process include the transportation and organization of vesicles Lehmler et al, 1997;Seiler et al, 1997;Steinberg & Schliwa, 1993Steinberg et al, 1998;Wedlich-Soldner et al, 2000;Wu et al, 1998), nuclei Herr & Heath, 1982;Kaminskyj et al, 1989;McKerracher & Heath, 1986;Meyer et al, 1988;Oakley & Morris, 1980;Oakley & Rinehart, 1985;Steinberg & Schliwa, 1993;Wedlich-Soldner et al, 2000;Wu et al, 1998), vacuoles (Allaway et al, 1997;Herr & Heath, 1982;Hyde et al, 1999;Shepherd et al, 1993;Steinberg et al, 1998), mitochondria Herr & Heath, 1982;Steinberg & Schliwa, 1993;Wu et al, 1998) and the endoplasmic reticulum (Wedlich-Soldner et al, 2002). However, direct structural evidence of MT and organelle interactions is rare (Heath, 1994).…”
Section: Organelle Positioningmentioning
confidence: 99%